2013
DOI: 10.2478/bvip-2013-0078
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the influence of selenium supplementation in organic and inorganic forms on oxidant/antioxidant balance in rat lungs

Abstract: The aim of the experiment was to compare the effect of two newly synthesised organic selenocompounds with that exerted by sodium selenite on oxidant processes in rat lungs. Total antioxidant status (TAS), activity of antioxidant enzymes -superoxide dismutase (SOD) and glutathione peroxidase (GPx), concentrations of non-enzymatic antioxidants -ascorbic acid (AA) and reduced glutathione (GSH), concentration of lipid peroxidation marker -malonyldialdehyde (MDA), as well as tissue concentrations of silicon and mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…All these results indicate that improvement of the effectiveness of the AHT in dogs with malignant tumours requires enhancement of antioxidative capacity. Such effects may be obtained by applying additional administration of constituents contributing to antioxidative capacity such as selenium, vitamin C, and vitamin E (21,24). The analysis of time-related changes of TAC in serum of dogs from the nonmalignant group demonstrated its significant improvement after one month of the AHT.…”
Section: Discussionmentioning
confidence: 99%
“…All these results indicate that improvement of the effectiveness of the AHT in dogs with malignant tumours requires enhancement of antioxidative capacity. Such effects may be obtained by applying additional administration of constituents contributing to antioxidative capacity such as selenium, vitamin C, and vitamin E (21,24). The analysis of time-related changes of TAC in serum of dogs from the nonmalignant group demonstrated its significant improvement after one month of the AHT.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidases are enzymes containing selenium (Se). The activity of GPx in the cells may increase until an adequate supply of Se in the diet maximizes the enzyme activity [46]. Apparently, the metabolites od DEL (3-PBA and Br 2 CA) do not pose a great risk to kidney functioning as creatinine concentrations in the blood sera were not elevated.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS can damage DNA, proteins, and lipids, and change a cell's metabolism, and affect gene expression and post-translational modifications of proteins, which accelerates ageing, neurodegeneration, and development of atherosclerosis, hypertension, type II diabetes, and cancer [26,27]. Superoxide dismuthase (SOD) and glutathione peroxidase (GPx) are antioxidant enzymes ubiquitous in living organisms acting as an endogenous defense against ROS [28,29].…”
mentioning
confidence: 99%
“…Even an application of antioxidants such as ascorbic acid or tocopherol did not protect yeast cells from the toxicity of the used PYRs (13). However, Musik et al (17) have shown that organic selenium compounds supplementation improved the oxidant/antioxidant balance in rats. The GPx are enzymes containing selenium.…”
Section: Discussionmentioning
confidence: 99%